2016
DOI: 10.1109/tim.2016.2599458
|View full text |Cite
|
Sign up to set email alerts
|

An In Situ Measurement System for Characterizing Orbital Debris

Abstract: This paper presents the development of an in situ measurement system known as the Debris Resistive Acoustic Grid Orbital Navy/NASA Sensor (DRAGONS). The DRAGONS system is designed to detect impacts caused by particles ranging from 50 micrometers to 1 mm at both low-earth and geostationary orbits. DRAGONS utilizes a combination of low-cost sensor technologies to facilitate accurate measurements and approximations of the size, velocity, and angle of impacting micrometeoroids and orbital debris (MMOD). Two thin l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Cultivation of different species of mushroom was initiated on experimental basis in the Botanical Garden of Sophitorium Institute of Technology and Life Skills, Khorda, Odisha by Modern Technology [2,3] . Annually, 100 class attendees were increase their knowledge by 50% on small-scale shiitake and oyster mushroom production.…”
Section: Methodsmentioning
confidence: 99%
“…Cultivation of different species of mushroom was initiated on experimental basis in the Botanical Garden of Sophitorium Institute of Technology and Life Skills, Khorda, Odisha by Modern Technology [2,3] . Annually, 100 class attendees were increase their knowledge by 50% on small-scale shiitake and oyster mushroom production.…”
Section: Methodsmentioning
confidence: 99%
“…Realistic hypervelocity impact tests have been successfully carried out. 6) The results showed that the sensor was able to accurately assess the size and location of the impact.…”
Section: Testing For Mirrored Impact Damage Readingmentioning
confidence: 98%
“…Design and functionality tests have been performed to validate the sensor performance, including hypervelocity tests. 6) However, there were concerns regarding the sensor's sensitivity to thermal fluctuations, launch vibration environment, and a secondary, induced damage due to particle impact. In order to characterize these potential problems, a series of tests have been performed to validate the design.…”
Section: Introductionmentioning
confidence: 99%